Motherhood: Ideal Stereotypes of Arab-Indonesian Mothers - Ramadhani, Muthia Anggita; Budhyono, Rasus; Subekti, Mega (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
PurposeThis study aimed to identify the construction of motherhood among Arab-Indonesian women in Depok. In addition, this article also analyzed the subjectivity of Arab-Indonesian mothers on Arab-Indonesian families in Depok. MethodThis research used field methods with interviews as a data collection technique. In addition to primary data obtained from the field, this research also used secondary data in the form of literature studies to complement data sources. The research was conducted by combining the research methods of cultural studies and gender studies. Results/FindingsThis research showed the form of construction of Arab mothers in Depok which was influenced by patriarchal culture. However, mothers of Arab descent acted as subjects in carrying out the mothering role. ConclusionThe construction of motherhood controled mothers to be able to perform the mothering role uniformly. Mothers were expected to be good mothers in regulating emotions, prioritizing children in everything, understanding and comprehending the family, trying for pregnancy, and getting pregnant at the right age. However, mothers do not necessarily follow the prevailing construction.